ORDERED PHASES IN THE EXTENDED HUBBARD-MODEL - Lagos, R. E. (Elsevier B.V., 1994)
A novel method to probe the diverse phases for the extended Hubbard model (EHM), including the correlated hopping term, is presented. We extend an effective medium approach [1] to a bipartite lattice, allowing for charge- and/or spin-ordered phases. We calculate the necessary correlation functions to build the EHM phase diagram.